Logistics in the Context of Industry 4.0 - Irina N. ROGOVA; Alexey S. KHARLANOV; Bolat B. IMANBAEV (Communications of International Proceedings, 2021)
The motivation for carrying out the presented study was a certain pattern noticed by the authors in changes in the field of logistics in the context of the global economic crisis, which has a direct impact on the implementation of Industry 4.0. The basic research methods which were used by us during research of theme were analysis and evaluation of the effectiveness of digital technologies, their impact on the level of competitiveness of the state which are the most involve into transformation process to Industry 4.0. Analysis of reports of domestic and foreign consulting companies on the digital transformation of business processes in the world's leading companies. Using such research methods as monographic, data synthesis, comparative, graphical representation of data, a strategic analysis of the transformation of business technologies in the logistics activities of modern enterprises is carried out. All methods we mentioned above helped us to identify the main features and stages of transformation of logistics technologies in the new world economy. In the article a list of certain factors and theirs' the level of effect on competitiveness of the state in the conditions of transformation are determined. In addition, the main features of industry 4.0 are identified. The main trends in the patterns of its development are presented. The main limitations that slow down the development of logistics approaches and the process of digital transformation are considered. Conclusions are made about the future of logistics in the conditions of widespread implementation of the principles of industry 4.0.
Keywords: Logistics; global economy; business process transformation.